2017
DOI: 10.5539/ies.v10n6p123
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Problem-Based Learning Strategy to Increase High Order Thinking Skills of Senior Vocational School Students

Abstract: This research is to apply and develop a strategy of problem-based learning to increase the ability of higher order thinking skills of senior vocational schools students. The research was done due to a fact that the quality of outputs of the senior vocational schools has not met the competency needed by the stakeholders in the field, that has made the outputs difficult to get jobs, or fail to run a private business of their own. This research is a quasi experiment applying Nonequivalent Control Group Design, do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 4 publications
0
20
0
4
Order By: Relevance
“…One of the skills required in the world of industry is HOTS [33]. However, today's VHS graduates lack the ability of HOTS because they received too many lessons in hard skills and lacks the development of thinking skills.…”
Section: Resultsmentioning
confidence: 99%
“…One of the skills required in the world of industry is HOTS [33]. However, today's VHS graduates lack the ability of HOTS because they received too many lessons in hard skills and lacks the development of thinking skills.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it seems clear that in contextual learning, students are given more opportunities to solve problems according to their needs and abilities. Furthermore, the results of research by Frank & Barzilai (2006) and Suprapto et al (2017), in problembased learning, students will learn to use appropriate judgment and analysis for problem solving that may be more than one solution, and feel the importance of cooperation between team members in the social environment aspects. Then, from the results of his research Komalasari (2012), findings were found that: First, contextual learning in Civic Education had a significant influence on citizenship skills for junior high school students in West Java, Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…Maka dari itu pendidikan berperan penting dalam membantu siswa mengembangkan keterampilan tersebut, misalnya dengan membuat mereka bertanggung jawab secara bersama-sama dengan guru atas pembelajarannya dan secara aktif melibatkan mereka dalam kegiatan pembelajaran (Van Beek et al, 2014). Dalam proses pembelajaran, peserta didik diharapkan mampu meningkatkan kompetensi kognitif, afektif, dan keterampilannya untuk mempersiapkan dirinya agar mampu menjalani kehidupan masa depan di masyarakat (Suprapto et al, 2017).…”
Section: Masyarakatunclassified